A cephalometric study of the tongue position in class III patients - Wilfredo Molina Wills; Vanessa Rodriguez (Journal of Dental Problems and Solutions - Peertechz Publications, 2019)
Aims: The objective of this study was to evaluate the tongue position during deglutition with respect to the occlusal plane in class III patients with teeth in centric occlusion. Methods: 24 lateral cephalometric radiographs of a group of 30 class III patients were randomly selected and divided into two Groups: The fi rst group for class III patients with open bite and the second group for class III patients with inverted overbite. The angles formed by the plane of the tongue and the occlusal plane obtained in all the samples were compared between the two studied groups. The T-test was used to evaluate the differences among studied angles. Results: The average of the anterior angles in patients with inverted overbite was lower than the average of the anterior-lower angles in class III patients with open bite. Anterior-lower angles with values between 24.17 and 34.08 were observed for class III with inverted overbite. T test of equality of means 6.661 signifi cance, the angles were signifi cantly different (p< .001) in both studied cases.